Functional Roles of Equine Infectious Anemia Virus Gag p9 in Viral Budding and Infection - Chen, Chaoping (American Society for Microbiology, 2001)
Previous studies utilizing Gag polyprotein budding assays with transfected cells reveal that the equine infectious anemia virus (EIAV) Gag p9 protein provides a late assembly function mediated by a critical Y(23)P(24)D(25)L(26) motif (L-domain) to release viral particles from the plasma membrane. To elucidate further the role of EIAV p9 in virus assembly and replication, we have examined the replication properties of a defined series of p9 truncation and site-directed mutations in the context of a reference infectious molecular proviral clone, EIAV(uk). Characterization of these p9 proviral mutants revealed new functional properties of p9 in EIAV replication, not previously elucidated by Gag polyprotein budding assays. The results of these studies demonstrated that only the N-terminal 31 amino acids of a total of 51 residues in the complete p9 protein were required to maintain replication competence in transfected equine cells; proviral mutants with p9 C-terminal truncations of 20 or fewer amino acids remained replication competent, while mutants with truncations of 21 or more residues were completely replication defective. The inability of the defective p9 proviral mutations to produce infectious virus could not be attributed to defects in Gag polyprotein expression or processing, in virion RT activity, or in virus budding. While proviral replication competence appeared to be associated with the presence of a K(30)K(31) motif and potential ubiquitination of the EIAV p9 protein, mutations of these lysine residues to methionines produced variant proviruses that replicated as well as the parental EIAV(uk) in transfected ED cells. Thus, these observations reveal for the first time that EIAV p9 is not absolutely required for virus budding in the context of proviral gene expression, suggesting that other EIAV proteins can at least in part mediate late budding functions previously associated with the p9 protein. In addition, the data define a function for EIAV p9 in the infectivity of virus particles, indicating a previously unrecognized role for this Gag protein in EIAV replication.